2022
DOI: 10.1101/2022.03.24.485587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vimentin intermediate filaments organize organellar architecture in response to ER stress

Abstract: Compartmentalization of organelles in space and time affects their functional state and enables higher order regulation of essential cellular processes. How organellar residence is maintained in a defined area of the cell remains poorly understood. In this study, we uncover a new role for intermediate filaments in the maintenance of organellar architecture and dynamics, which is executed through a functional connection between Vimentin and the ER-embedded ubiquitin ligase ring finger protein 26 (RNF26). While … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
4
1
0
Order By: Relevance
“…How vimentin IFs provide support to the Golgi remain to be determined, but an attractive hypothesis is that they form a cage or meshwork around the organelle, which provides a mechano-protective function. This would be analogous to what has been reported for the nucleus and other cytoplasmic organelles (Cremer et al, 2022; Etienne-Manneville, 2018). The Golgi ribbon, by virtue of its localization adjacent to the nucleus, may be embedded within the IF meshwork that forms a cage around the nucleus (Cremer et al, 2022; Etienne-Manneville, 2018).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…How vimentin IFs provide support to the Golgi remain to be determined, but an attractive hypothesis is that they form a cage or meshwork around the organelle, which provides a mechano-protective function. This would be analogous to what has been reported for the nucleus and other cytoplasmic organelles (Cremer et al, 2022; Etienne-Manneville, 2018). The Golgi ribbon, by virtue of its localization adjacent to the nucleus, may be embedded within the IF meshwork that forms a cage around the nucleus (Cremer et al, 2022; Etienne-Manneville, 2018).…”
Section: Resultssupporting
confidence: 90%
“…This would be analogous to what has been reported for the nucleus and other cytoplasmic organelles (Cremer et al, 2022;Etienne-Manneville, 2018). The Golgi ribbon, by virtue of its localization adjacent to the nucleus, may be embedded within the IF meshwork that forms a cage around the nucleus (Cremer et al, 2022;Etienne-Manneville, 2018). This would certainly be consistent with our imaging data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that scenario T3F, irreversible trapping with spatially dependent trapping, is unambiguously the best scenario out of the scenarios considered. The spatial profile of the trapping rate, particularly where it increases towards the cell center, is consistent with existing studies showing vimentin interaction with organelles, including the nucleus [54][55][56][57][58]. Furthermore, recalling that α(r) in this case is a net trapping rate, the negative values of α(r) towards the cell edge suggest that vimentin trapping is reduced at the cell periphery, possibly indicating a lower number of attachment sites for trapping [Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Again considering all scenarios, the poor ranking of the constant-velocity and quantity-dependent velocity assumptions relative to the spatially dependent assumptions T3E and T3F is consistent with the biological observations of spatially dependent retrograde flow of actin [19] and the underlying compartmentalization of cell organelles interacting with vimentin [54][55][56][57][58], respectively. Because both scenarios are biologically plausible, we examine them in more detail.…”
Section: B Model Selection Resultssupporting
confidence: 70%